Dissecting Corporate Liability in Environmental Crimes in the 2023 Criminal Code: An Identification Theory Perspective - Rohmat (Universitas Negeri Semarang, 2025)
Development and modernization in the contemporary era of globalization drive social changes across various domains. Advancements can be observed in economic, technological, and social sectors, often initiated by corporations. While corporations contribute to societal economic progress, they may also engage in deviant conduct driven by economic interests. Consequently, organizations involved in industrialization may cause harm to others and should be held accountable for their actions. This study employs normative legal research methodologies, utilizing both legislative and historical approaches. The legal materials used comprise primary and secondary sources, which are analyzed using a descriptive-analytical technique. The Industrial Revolution spurred the development of regulations concerning corporate liability. However, in Indonesia, Dutch influence initially restricted corporate criminal liability solely to its management. In the most recent National Penal Code, corporations are now recognized as entities liable for criminal offenses. Regarding criminal liability for environmental offenses, two models exist: the first attributes responsibility solely to the company as the offender, while the second holds both the corporation and its management accountable. The second model aligns with the identification theory.